Cover Picture: nido‐Dicarbaborate Induces Potent and Selective Inhibition of Cyclooxygenase‐2 (ChemMedChem 2/2016). Issue 2 (19th January 2016) - Neumann, Wilma; Xu, Shu; Sárosi, Menyhárt B.; Scholz, Matthias S.; Crews, Brenda C.; Ghebreselasie, Kebreab; Banerjee, Surajit; Marnett, Lawrence J.; Hey‐Hawkins, Evamarie
Abstract : The front cover picture shows the pronounced impact of a nido ‐dicarbaborate cluster on the binding mode of a cyclooxygenase (COX) inhibitor. The commercially available COX‐1‐selective inhibitor indomethacin was converted to a highly potent and selective inhibitor ( nido ‐indoborin) of the pathogenic isoform COX‐2 by replacing the chlorophenyl ring with a boron cluster. Introduction of the cluster leads to a binding mode in the COX‐2 site in which the indole moiety is flipped, compared with the orientation of indomethacin. Remarkably, the cluster opens up a subpocket by causing rotation of a leucine residue. The nido cluster is a promising pharmacophore and increases the stability and solubility of the inhibitor. More information can be found in the Communication by Evamarie Hey‐Hawkins et al. onpage 175 in Issue 2, 2016 (DOI:10.1002/cmdc.201500199 ).